Aplicación móvil para el servicio de transporte de mototaxis en la ciudad de Iquitos, 2024 - Dávila Jesus, Maick Junior (2025)
In Iquitos, Mototaxis are one of the most commonly used means of urban transport in Iquitos; however, the traditional service presents problems related to safety, informality, and limited customer care, which negatively affect perceived service quality. This study aimed to determine the influence of a mobile application on the quality of mototaxi service in Iquitos during 2024, based on user perception. A pre-experimental design was applied with a sample of 60 users: 30 evaluated the traditional service and 30 used the mobile application. Data were collected through a questionnaire based on the SERVPERF model, which includes the dimensions of tangibility, reliability, responsiveness, security, and empathy. Descriptive statistics and the Student’s t-test were used for data analysis. The results showed significant differences between both modalities. In the traditional service, most users reported a neutral perception (83.3%), whereas 96.7% of users of the mobile application rated the service as favorable. The mean perception score increased from 63.5 to 79.3 points, showing a statistically significant difference (t = -9.083; p < 0.001). It is concluded that the use of a mobile application positively influences the quality of mototaxi service in Iquitos, providing users with a safer, more reliable, and more satisfactory experience.